Social support and its relationship to the level of achievement of high school students in Jordanian public schools - Al-Faleh, Samar Fahed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the level of social support (support by friends, support from the family, support by the teacher), and to analyze the relationship between social support and achievement among students of High school students in government schools. The study followed descriptive analytical approach based on a questionnaire applied to 137 students of Karak government schools. The study found that the students get moderate level of social support; the study showed that the level of friends support came first, followed by teacher support, followed by family support, and found a relationship between social support and achievement in Students of Karak government schools. In light of the results, the study recommended several recommendations, the most important of which is to sensitize parents and faculty members about the importance of social support.
Keywords: social support; level of achievement; High school students; government schools